Approximation of the crack-tip field in fatigue cracks in bridge steel specimens: DIC analysis of different constraint levels (Fracture and Structural Integrity, 2019)
A study on the accuracy of the approximation of the displacement field around of crack tip in a sample made from bridge steel (S355) is main objective of contribution. Linear elastic fracture mechanics (LEFM) theory in framework of multi-parameter formulation, i.e. postulated by Williams is used to determine of coefficients of Williams power series terms. Over deterministic method was used to calculate the terms based on the least squares regression technique, applied on data from numerical simulation and experiment on S355 steel grades. Comparison between the stress fields (by principal stress s1 and von Mises stress sHMH) obtain from experimental measurement DIC, Hybrid method and obtain from reconstruction by using various number of Williams power terms are quantified in order to get key information around the crack tip region on bridge steel specimens.
Keywords: Displacement; Crack-tip stress fields; DIC; High order terms; Multi-parameter approximation accuracy; Williams power series